PENGARUH LIMBAH CAIR NANAS (LCN) TERHADAP PERTUMBUHAN DAN KADAR OMEGA 3 Chlorella sp - Handayani, Tut Wuri; Sutanto, Agus (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2016)
This research was conducted at the Integrated Hard Science Laboratory of Muhammadiyah University of Metro on August 16 to September 1, 2016. The observation and data recording was carried out for 10 days. The study used RAL design (Complete Random Design). The sample consisted of 6 treatments with 4 replications. The pineapple liquid waste (PLW) given are various in concentrations, namely 0% (as a control), 20%, 40%, 60%, 80% and 100%, with 5ml culture of Chlorella sp added to each. The data were analyzed with Normality Test, Homogeneity Test and Multi Variat Test. The analysis was performed by using SPSS.21 application. From this analysis, It can be concluded from throughout research data analysis the Chlorella sp growth rate made sigmoid pattern of growth, relevant with the existing theories of rate of growth. The greater the concentration of PLW added to the culture medium, the greater the opportunity for Chlorella sp to be able to grow and flourish. It can be seen in the culture medium of 100% PLW which has exceeded the level of cell density in culture media of 0% PLW (control) as much as 2.13 x106 cells /ml. Of the various treatments with various PLW concentrations on the growth of Chlorella sp it was found that the highest population density is in the culture medium of 100% PLW. Of the various treatment with various PLW concentration it was found the highest amount of omega-3 Chlorella sp is in the culture medium of  60% PLW, i.e. 5, 1%